Measurement of radiation damage in ceramics and its application to age determination - Tite, M (1965)
The effects of high energy radiation on ancient ceramics, as observed through the measurement of the resulting thermoluminescence, is reported and the possibility of using thermoluminescence measurements to determine the age of the ceramics is investigated. The radiation effects considered are the filling of excising electron and hole traps and the creation of new traps since a knowledge of the relative importance of these two effects is essential for age determination. Trap filling and trap creation are investigated principally by means of rate curves (i.e. the plot of the thermoluminescence acquired versus the radiation dose). Evidence for trap creation is forthcoming in the case of X-rays and alpha particles but not in the case of beta particles. The fact that the X-ray rate curves can be resolved into saturating and linearly increasing components provides the first indication that X-rays create new electron and hole traps in addition to filling those already present. However this result is not conclusive since a linearly increasing component can arise from the filling of traps with a very low capture cross-section. The increase in the saturation level observed for samples, which are pre-irradiated with X-rays and then thermally bleached, provides more conclusive evidence for trap creation by X-rays. It is shown that the measurement of the saturation level after pre-irradiation and thermal bleaching is necessary since the susceptibility to small X-ray doses is increased as a result of competition phenomena, in addition to any increase occurring as a result of trap creation. The competition phenomena are investigated in more detail using beta particles, A model involving high temperature traps, which are not bleached by heating to 600°C and which have a high capture cross-section compared to traps associated with the 20-500°C range, is proposed to explain these competition phenomena. This model also provides an explanation for the non-linearity of the beta particle rate curves observed for small radiation doses. The alpha particle rate curves can, in some temperature regions, be resolved into saturating and linearly increasing components while, in other regions, the thermoluminescence reaches a maximum value and with further irradiation decreases continually. Again the form of the rate curves does not, by itself, prove that trap creation is occurring but conclusive evidence is provided, as in the case of X-rays, by pre-irradiation experiments. On the basis of the simple model which is proposed, approximate quantitative agreement is obtained between the pre-irradiation experiments and the alpha particle rate curves. By comparing the slope of the linearly increasing component of the alpha particle rate curves with the saturation level, it is shown that, for typical pottery, the number of new traps created since firing, by the natural radioactivity of the sherd, is small compared to the number of traps already existing. In addition there is no obvious method of distinguishing these newly-created traps from the remainder since annealing also produces changes in the luminescence efficiency of the material. Hence it is seen that age determination, based on the number of traps created since firing, is not practical and that the only approach available is through the measurement of the number of traps filled since firing. In determining the age of the pottery from the number of traps filled, the susceptibility (i.e. the number of traps filled per unit of absorbed energy) of the sherd to alpha, beta and gamma radiation must be measured. Since the filled traps cannot be emptied without changing the luminescence efficiency of the sherd, measurements are made on the untreated sherd. The resulting inaccuracies introduced into the value obtained for the susceptibility, because of the non-linearity to alpha and beta particles. Irradiations using a solution of Ra224 in alcohol show that the alpha particle susceptibility is provided by the age determination results themselves. It is noted that for successful age determination measurements, based on the number of traps filled, the glow curves (i.e. the plot of the thermoluminescence emitted versus temperature) must be measured in nitrogen otherwise spurious thermoluminescence, not due to radiation-filled traps, appears. It is further noted that, after grinding, the sample must not be exposed to light otherwise the thermoluminescence is bleached, This method of age determination also depends on the fact that the high temperature traps, at least have not been thermally bleached during the centuries of burial. It is shown by trap depth measurements an thermal bleaching experiments on artificially irradiated samples that this assumption is justified for traps associated with the 350-500°C range. An age determination programme using seven groups of sherds of known archaeological age is described. The beta particle susceptibility is measured and on the basis of the Ra224 results, the alpha particle susceptibility is assumed to be one tenth of this. This assumption provides an absolute age for the sherds in approximate agreement with the archaeological age whereas, if the alpha and beta particle susceptibilities are assumed equal, the absolute age obtained is approximately one fifth of the archaeological age. These results show that thermoluminescence measurements, based on the number of traps filled since firing, provide an essentially valid method of age determination and considering the possible sources of error, the agreement obtained is remarkable. However it appears, at the moment, that the non-uniform rate of acquisition of thermoluminescence constitutes an insuperable barrier to more precise age determination by this technique.